THE TEMPERATURE OF THE PLANET EARTH IN LATITUDE 850-250 DEGREES NORTH (Web of Technology: Multidimensional Research Journal, 2025)
In the past, hydrometeorology took into account the total thermal impact of radiation on certain geospheres. At the same time, the magnitude of this radiation flux outside the Earth was assumed to be constant.